Longitudinal associations between dietary quality and Alzheimer’s Disease genetic risk on cognitive performance among African American adults - Hossain, Sharmin (Br J Nutr, 2020)
Poor diet quality is associated with poor cognition and increased neurodegeneration, including Alzheimer’s disease (AD). We are interested in the role of diet quality on cognitive functioning (by sex and increasing genetic risk for AD), in a sample of African American (AA) middle-aged adults. We analyzed a sub-group of participants (~55% women; mean follow-up time~4.7y) from the Healthy Aging in Neighborhoods of Diversity across the Life Span (HANDLS) study with a genetic risk score for AD (hAlzScore). The Healthy Eating Index (HEI-2010), Dietary Approaches to Stop Hypertension (DASH), and the Mean Adequacy Ratio (MAR) computed at baseline (2004–2009) and follow-up visits (2009–2013) were used to assess initial diet quality (DQ) and change over time. Linear mixed-effects regression models were utilized, adjusting for select covariates, selection bias and multiple testing. DQ change (ΔDQ) was associated with California Verbal Learning Test- List A (CVLT- List A) - overall (0.15±0.06, p=0.008) and in women (0.21±0.08, p=0.006), at highest AD risk, indicating protective effects over time. Greater AD risk was longitudinally associated with poorer Clock Command Test scores in men. Poor diet quality was positively and cross-sectionally associated with Trails B scores, but in women only. Better-quality diet was associated with a slower decline in verbal memory among AA women, with greater AD risk. Insufficient clinical evidence and/or mixed findings dictate the need for more studies are needed to investigate brain morphology and volume changes in relation to diet quality in an at-risk population for AD, over time.